Between tradition and appropriation: mythical method and politics in the poetry of George Seferis and Yannis Ritsos. (17th September 2016) - Tziovas, Dimitris
Abstract: Venerating the past in the form of tradition and adapting or appropriating it for modern purposes could be seen as two modes of engagement with antiquity, involving a certain hierarchy, either privileging the authority of the past or assigning priority to the present in radically recasting the ancient material. This article will explore whether in the interstices between tradition and appropriation it is possible to position/locate a third approach which would not involve a reverence for the past or radical revisioning of the classical material but could generate a dialogue between source and adaptation, with the aim of encouraging their mutual illumination. It will consider the extent to which this dialogic or interactive mode of classical reception has proved more appealing to modern Greek poets dealing with conceptions of history, time and politics and explore its epistemological implications by focusing on 'mythological' poems by George Seferis and Yannis Ritsos that allude to the political developments of the period in which they were written and engage with the past in different ways.